The impact of cross border M&As on company performance from emerging market: empirical evidence from China - Qian, Yiwen (2013)
This study is arranged according to three main research tasks: (i) To test short-run announcement wealth effects of Chinese OMAs in stock markets by event study. (ii) To investigate the determinants of OMA announcement effects by cross-sectional regression. (iii) To evaluate the three years company performance after OMA by financial ratio analysis. Findings report highly significant negative abnormal returns around six selected event windows around announcement date in terms of shareholder value and declining trend in financial ratios in three years after OMA activity. No significant result is discovered from hypothesis testing for determinants of negative abnormal returns.